Different Types of Intermittent Fasting for Glucosa Index Control in Diabetics: A Systematic Review - Asbath; Faridah Mohd Said (Universitas STRADA Indonesia, 2024)
Background: The glucose index is an important parameter in diabetes management and general health. Intermittent fasting has become an interesting research topic in an attempt to control glucose index. This study Glucose index is an important parameter in diabetes management and general health. Intermittent fasting has become an interesting research topic in an attempt to control glucose index. Purpose: This study aims to conduct a systematic review of the different types of intermittent fasting and their impact on glucose index control. Method: The research method used was a thorough literature search in scientific databases such as PubMed, Google Scholar, and ScienceDirect for articles investigating different types of intermittent fasting in the context of glucose index control. We evaluated these articles based on their methodological quality and identified key findings. Results: The results of this systematic review showed that different types of intermittent fasting, including 16/8 fasting, 5:2 fasting, daily fasting, and full-day fasting, have varying impacts on glucose index control. Some studies showed significant reductions in fasting blood glucose levels, improved insulin sensitivity, and decreased insulin resistance. However, the results may vary depending on the duration of fasting, the type of food consumed during the feeding period, and individual characteristics. Conclusion: suggests that intermittent fasting could be a potentially effective strategy in glucose index control. However, more studies need to be conducted to better understand which type of intermittent fasting is most effective and safe for individuals with various health conditions.